Caffeine supplementation in cyclists: performance outcomes, physiological responses and interactions – a narrative review - Moćko, Paweł Krzysztof; Ogorzałek, Filip Maciej; Polczyk, Jakub; Deptuch, Wojciech; Golińska, Zofia; Zając, Maciej Tomasz; Drelich, Krzysztof; Rajzer, Przemyslaw; Rurkowska, Julia; Szczuciński, Wiktor (Quality in Sport, 2026)
Background Cycling is a highly demanding endurance sport, in which small improvements in performance may significantly influence results. Caffeine is one of the most commonly used ergogenic aids among athletes, due to its potential to enhance physical performance and delay fatigue. Understanding its effects on cycling performance and physiological responses is important for both athletes and sports science practitioners. Aim The aim of this narrative review was to evaluate the effects of caffeine supplementation on cycling performance and physiological responses in cyclists, as well as to analyse the potential mechanisms underlying its ergogenic effects. Materials and Methods This narrative review is based on a literature search conducted using the PubMed database. The search was conducted using keywords related to caffeine, cycling and cycling performance. Filters were used to identify clinical trials published from 2016 onward. This led to 54 publications. After manual full-text analysis 25 articles found with the mentioned search were included. Results and conclusions The studies showed that caffeine administered orally in various forms is effective in improving performance in endurance and time-trial protocols. Its effect in short-duration maximal exercise tests was observed, although the results are inconclusive. Several studies reported increased blood lactate concentrations and reduced perceived exertion following caffeine ingestion. Evidence suggests that central nervous system mechanisms contribute substantially to the ergogenic effects of caffeine. Doses of 2.7–6 mg/kg administered approximately 60 minutes before exercise were most commonly associated with performance benefits. Current evidence does not demonstrate additive ergogenic effects of caffeine when combined with other ergogenic substances. Heat, time of day, habitual caffeine consumption and abstinence and genetic factors may influence ergogenic effects of caffeine.